A monosymptomatic Melkersson-Rosenthal Syndrome in an 8 years old boy - Dodi, I.; Verri, R.; Bravi, et al., B. (Acta Biomedica Atenei Parmensis, 2006)
Melkersson-Rosenthal Syndrome (MRS) is a systemic neuro-mucocutaneous granulomatous disease, characterized in its classical form by a triad of recurrent facial nerve paralysis, swelling of the lips and lingua plicata. However, this classical triad is rarely present, while the monosymptomatic or oligosymptomatic forms are more frequent. The presence of two or one of the manifestations mentioned above, with granulomatous cheilitis in the biopsy, is sufficient to make the diagnosis of monosymptomatic or oligosymptomatic form of MRS. This syndrome is very rare in childhood, instead, it is more frequent in young adults between the second and third decades of life.We present the case of an 8 years old boy who was brought to us because of a non painful swelling of the upper lip, associated with gingival hypertrophy, that had persisted for more than two months. Given the negative results of the hemato-chemical and instrumental assessments, we performed an upper lip biopsy whose histological study showed granulomatous cheilitis.We diagnosed this case as a monosymptomatic MRS and administered an intralesional steroid therapy using triamcinolone, with complete recovery.